How Newspapers in Kansas Are Using News Releases from K-State Research and Extension - Pat Melgares; Tracy Rutherford; Lori Alexander (Journal of Applied Communications, 2003)
This study looks at how newspaper editors in Kansas use news releases from Kansas State University Research and Extension (KSRE), which distributes more than 700 news releases annually to newspapers across the state. An analysis of clippings over 10 weeks showed that editors rarely change the original text or headline in KSRE news releases, and more than half of the releases were published within 10 days of release. KSRE news releases were published in all regions of Kansas. Using a formula to determine the advertising equivalency value of news clips, the data indicates a value of 33,286.94 for the sample studied. The findings provide one way in which to report accountability to the organization’s administrators, as well as a better understanding of possible areas of improvement for the KSRE news office.